Cover Image. Issue 10 (8th September 2020) - Meyer, Annika; Roof, Scott; Gray, Mingyang L.; Fan, Caleb J.; Barber, Brittany; Miles, Brett A.; Teng, Marita; Genden, Eric; Rosenberg, Joshua D.
Abstract : The cover image is based on the Original Article Thermal imaging for microvascular free tissue transfer monitoring: Feasibility study using a low cost, commercially available mobile phone imaging system by Annika Meyer MD et al., https://doi.org/10.1002/hed.26350 .